An Exploration of EFL Students’ Learning Autonomy in the Context of TOEFL Preparation at Jabal Ghafur University - Jamaliah Jamaliah; Ahmad Diauddin; Zaiturrahmi Zaiturrahmi (Fakultas Keguruan dan Ilmu Pendidikan Universitas Jabal Ghafur, 2026)
This study explores the autonomy of English as a Foreign Language (EFL) students in preparing for the TOEFL test. It aims to examine students’ perceptions of autonomous learning and identify effective strategies that contribute to their TOEFL readiness. Employing a qualitative approach, data were collected through semi-structured interviews with ten English education students at Jabal Ghafur University who had taken TOEFL preparation classes. Thematic analysis was used to interpret the data. The results revealed that students engaged in various self-regulated learning strategies, including creating study plans, using digital resources such as YouTube and learning apps, and practicing with mock tests. Students highlighted the importance of independent learning outside the classroom to improve comprehension and test performance. The study concludes that learner autonomy plays a crucial role in supporting students’ success in TOEFL preparation and enhancing their English proficiency. These findings offer insights into how autonomous learning can be encouraged in EFL contexts.Keywords: autonomy; EFL learners; learning strategies; self-regulated learning; TOEFL preparation